(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Outline of contents: In the article there was presented essence and methods of creating cents of the costs and stages of creating. Described budgeting of the costs in cents of costs.Furthermore,the principles and evaluation measures of the results of costs centres were appeared.